Indonesia Memilih Presidensial - Amalia, Luky Sandra (Pusat Penelitian Politik, 2009)
Based on the Indonesian constitution (Undang-Undang Dasar 1945), Indonesia decided to undertake presidential system since this system gives large proportion for president to create prosperities for its citizens. The preamble of UUD 1945 also consist ofcriteriafor being a good Indonesian president such as the president must be able to create public prosperities, to improve Indonesian people's intelligence, to make social justice for all citizens, to protect all citizens, and to make the world order. However, before the candidates are elected as president and vice president, they have to conduct political campaign in order to make Indonesian people aware of their programs and track records. The political campaign includes mass media campaign and interpersonal campaign. In this regards, the presidential election is a political education for all people indeed.